Use of social media for communicating about critical care topics: A Norwegian cross‐sectional survey. Issue 10 (6th August 2019) - Petosic, Antonija; Sunde, Kjetil; Beeckman, Dimitri; Flaatten, Hans K.; Wøien, Hilde
Abstract : Background: Social media (SoMe) might be an alternative platform for communicating critical care topics to implement evidence‐based practice in the intensive care unit (ICU). This survey aims to describe ICU nurses' and physicians' use of SoMe in general, and their perception of using closed Facebook‐groups for receiving content on critical care topics. Methods: A cross‐sectional, web‐based, anonymous survey was distributed to ICU physicians and nurses in four ICUs in autumn 2017 via an email‐campaign. Descriptive statistics with rates, percentages and median numeric rating scale (NRS) scores, interquartile ranges are presented. Results: The response‐rate was 64% (253/ 394) including 210 nurses and 43 physicians. Overall, 93% had a SoMe‐profile, and 77% had a profile on more than one network site. Facebook was the most used social network site, with 87% having a profile. Totally, 68% were daily users, but more nurses used Facebook daily vs physicians (81% vs 60%, respectively, P = 0.006). Nurses were also more positive toward being members of closed Facebook‐groups aimed to exchange content on critical care topics (median NRS 9 (6‐10) vs 6 (3‐9), respectively, P = 0.014). Conclusion: The majority of ICU nurses and physicians were active SoMe users, mainly for personal purposes, and Facebook was the most popular SoMe. Nurses used Facebook daily more frequent and were more positive toward content on critical care topics on Facebook than physicians. These findings might be relevant to customize future communication about critical care topics via SoMe.